An analysis of the evaluation of the fracture energy using the DCB-specimen (Archives of Mechanics - Test, 2007)
The methods to estimate the fracture energy using DCB-specimens as advocated in common standards. For instance, ASTM D 3433 and BS 7991:2001 are based on a compliance method, i.e. on linear elastic fracture mechanics (LEFM). Since the mechanical properties of almost all adhesives are non-linear, errors are generated. In some of the standards, the non-linear behaviour is compensated for by the use of correction terms generated from the experiments. An analysis of the methods of evaluation the fracture energy from experiments is performed. This analysis is performed first by simulating an experiment using realistic data for an engineering adhesive and then, by analysing the results with different methods. In this way, the correct fracture energy is known beforehand and the error in the evaluated fracture energy can be determined. In the present work it is shown that the magnitude of this error depends on the length of the crack. The results show that some commonly used methods generate substantial errors when a large region of non-linear deformation precedes the crack tip. It is also shown that methods based on nonlinear fracture methods do not produce this kind of error.